2015
DOI: 10.1002/etc.3198
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic toxicity of the ionic liquid 1‐octyl‐3‐methylimidazolium chloride on earthworms (Eisenia fetida)

Abstract: Ionic liquids also known as "green solvents," are used in many fields. However, the dispersion of ionic liquids in soil systems is likely to cause damage to soil organisms. The objective of the present study was to investigate the toxicity of 1-octyl-3-methylimidazolium chloride ([C8 mim]Cl) on earthworms (Eisenia fetida). For this purpose, earthworms were exposed to different concentrations of [C8 mim]Cl (0 mg/kg, 5 mg/kg, 10 mg/kg, 20 mg/kg, and 40 mg/kg artificial soil) and sampled at 7 d, 14 d, 21 d, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…For other groups of organisms, the actual mode of action has received less attention and is accordingly less well understood. There is ample evidence that ILs induce oxidative stress in many different organisms including algae, mussels, earthworms, plants, and fish . DNA damage has also often been reported but is usually explained as a direct consequence of the increased reactive oxygen species (ROS) content. , It should be noted that the direct interaction of ILs with DNA can also be very strong due to multiple interactions with both the phosphate backbone and the nucleobases .…”
Section: Structural Design For Less-(eco)toxic Ilsmentioning
confidence: 99%
“…For other groups of organisms, the actual mode of action has received less attention and is accordingly less well understood. There is ample evidence that ILs induce oxidative stress in many different organisms including algae, mussels, earthworms, plants, and fish . DNA damage has also often been reported but is usually explained as a direct consequence of the increased reactive oxygen species (ROS) content. , It should be noted that the direct interaction of ILs with DNA can also be very strong due to multiple interactions with both the phosphate backbone and the nucleobases .…”
Section: Structural Design For Less-(eco)toxic Ilsmentioning
confidence: 99%
“…In addition, the degree of DNA damages ignificantly increases with an increasei nt he [omim]Clc oncentrationa nd exposure time. [172] Wu et al [173] have observed that the addition of DMSO,a saradical scavenger,r educes C. elegans lethality and decreasesR OS levels. The length of the alkyl sidec hain also substantially influencest he toxicity of ILs, with longera lkyl chains generating highert oxicity.…”
Section: Others Species Of Living Organismsmentioning
confidence: 99%
“…In particular, the SCGE when applied on earthworms has resulted as a high sensitivity bioassay for evaluating the genotoxic damage induced for wide group of pollutants. Among them, metals [22][23][24][25] polycyclic aromatic hydrocarbons [23] and other organic compounds [26], ionic [27] and, overall, several pesticides [28][29][30][31][32] ex vivo treatments, a non-invasive extrusion method was used for collecting earthworm coelomocytes according to Di Marzio, et al [23]. Earthworms were rinsed in tap water at RT and placed on a damp paper towel overnight to void gut contents during the extrusion procedure.…”
Section: Test Organismmentioning
confidence: 99%